Community-based theatre: Critical pedagogy for promoting social connectedness recovery in the post-pandemic era - Lulu Jiang; Farideh Alizadeh (Cogent Arts & Humanities, 2023)
The long-term impact of the COVID-19 pandemic has persisted for several years. After a period of prolonged social isolation, people may be especially vulnerable to developing issues, such as social withdrawal. Theatre has been utilised in some instances to inspire individuals to foster critical thinking and encourage them to lead a positive life. This study applies a community-based theatre test case to examine theatre practices within the framework of critical pedagogy to address emerging issues in the post-pandemic era. It aims to deliberate upon the ongoing process of the theatre workshop as well as the efficacy of theatrical approaches on an individual’s personal, interpersonal and sociological difficulties. This is meant to gain a better understanding of theatre practices that operate on the edge between critical pedagogy and sociocultural intervention. The findings suggest that community-based theatres effectively inspire participants to reflect on and take action to escape oppression. Therefore, it is an innovative strategy for promoting social connectedness while supporting post-pandemic responses. This study contributes to the theoretical, practical, and experiential development of critical pedagogy by providing support for individuals, groups, and the society.